2020
DOI: 10.1093/pcmedi/pbaa023
|View full text |Cite
|
Sign up to set email alerts
|

How to deal with the negative psychological impact of COVID-19 for people who pay attention to anxiety and depression

Abstract: Background The fear of insecurity and uncertainty caused by 2019 coronavirus disease (COVID-19), the separation and loss of certain important relationships, and the great changes in lifestyle have awakened strong emotional responses, which may cause psychological problems to the general population. However, there are few researches on how people who pay attention to anxiety and depression cope with negative psychological during the epidemic or major disaster. This study aimed to identify what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
1
2
0
4
Order By: Relevance
“…Our findings expand on previous observations regarding the mental health effects of the COVID-19 pandemic among social media users by presenting a more complete picture of health-related topics discussed on social media [ 18 ]. Our results not only confirm the findings from previous studies that showed high levels of anxiety and depression mentioned by social media users during the pandemic [ 35 , 36 ] but also revealed that the frequency of anxiety and other general health symptom–related posts, including generalized pain, weight loss, and fatigue, was significantly correlated with daily COVID-19 statistics. These data support the idea that social media represents a potential powerful source of information for health care professionals to draw real-time estimations about population health status [ 18 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings expand on previous observations regarding the mental health effects of the COVID-19 pandemic among social media users by presenting a more complete picture of health-related topics discussed on social media [ 18 ]. Our results not only confirm the findings from previous studies that showed high levels of anxiety and depression mentioned by social media users during the pandemic [ 35 , 36 ] but also revealed that the frequency of anxiety and other general health symptom–related posts, including generalized pain, weight loss, and fatigue, was significantly correlated with daily COVID-19 statistics. These data support the idea that social media represents a potential powerful source of information for health care professionals to draw real-time estimations about population health status [ 18 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…A kínai felmérések már a járvány kezdetén kimutatták, hogy a populáció közel felénél alakultak ki a járványhelyzet okozta pszichológiai distressz tünetei, míg közel egyharmaduknál közepes vagy súlyos szorongásos, közel egyhatoduknál pedig közepes vagy súlyos depressziós tüneteket észleltek [27]. Más vizsgálatok pedig még magasabb arányokat találtak [28]. A pandémia európai elterjedését követően hasonló arányszámokról számoltak be olasz, spanyol és cseh vizsgálatok is: a populáció közel harmada súlyos stressztünetektől szenvedett, és jelentős növekedést észleltek a szorongásos-depressziós tünetek és a poszttraumás stressz zavar gyakoriságában is [3,29,30].…”
Section: A Pandémia áLtalános Mentálhigiénés Hatásaiunclassified
“…Ezen eredmények szerint a depresszió négyszer, a szorongás háromszor volt gyakoribb, mint a megelőző évben, a suicid gondolatok aránya pedig a kétszeresére nőtt [34]. Kiemelésre érdemes, hogy a depressziós tünettan különösen az alacsony jövedelmű, hátrányos helyzetű, aktuális veszteséget (például állásvesztést) elszenvedett embereket érintette [28,33]. A pszichológiai distressz hátterében a leggyakrabban a vírusfertőzés miatti aggodalom (65,9%), a munkahely elvesztésétől való félelem (65,1%) és az anyagi gondok (60,6%) szerepeltek.…”
Section: A Pandémia áLtalános Mentálhigiénés Hatásaiunclassified
See 2 more Smart Citations